Analisis Yuridis Normatif terhadap Impunitas dalam Kasus Kekerasan Fisik pada Wartawan: Ditinjau dari UU No. 40 Tahun 1999 tentang Pers - Eviona Elshadai Margareth Hutapea; Trissa Lihayati Nur Laila (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
Physical violence against journalists remains a serious threat that hinders the functioning of democracy in Indonesia. Law Number 40 of 1999 concerning the Press explicitly guarantees legal protection for journalists through Articles 8 and 9, which emphasize freedom from censorship and the right to seek and disseminate information. However, criminal law enforcement against perpetrators of physical violence has not been optimal, leading to a culture of impunity. This study uses a normative juridical approach by analyzing the Press Law regulations, the provisions of the Criminal Code on assault (Articles 351-355), as well as the theoretical basis of Satjipto Rahardjo's preventive-repressive legal protection and Moeljatno's law enforcement principles. The results of the study indicate a significant gap between strong legal norms and weak enforcement practices, characterized by the dominance of mediation by the Press Council and a culture of impunity for perpetrators, often involving state apparatus. According to AJI reports from 2020-2025, there have been 84 to 89 cases annually, with only 15-20% processed criminally. The main obstacles include a lack of coordination between institutions, minimal awareness of law enforcement officials, victims' reluctance to report due to social pressure and fear of reprisals, and institutional solidarity among perpetrators. This impunity not only traumatizes journalists but also induces self-censorship, reduces investigative journalism quality, and weakens democratic checks and balances. Recommendations include revising the Press Law for stricter sanctions, enhancing law enforcement training, and establishing independent investigation teams under Komnas HAM to combat impunity effectively.